2013
DOI: 10.1002/anie.201307025
|View full text |Cite
|
Sign up to set email alerts
|

Class III Delocalization in a Cyanide‐Bridged Trimetallic Mixed‐Valence Complex

Abstract: The NIR and IR spectroscopic properties of the cyanide-bridged complex, trans-[Ru(dmap)4 {(μ-CN)Ru(py)4 Cl}2 ](3+) (py=pyridine, dmap=4-dimethylaminopyridine) provide strong evidence that this trimetallic ion behaves as a Class III mixed-valence species, the first example reported of a cyanide-bridged system. This has been accomplished by tuning the energy of the fragments in the trimetallic complex to compensate for the intrinsic asymmetry of the cyanide bridge. Moreover, (TD)DFT calculations accurately predi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
75
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(84 citation statements)
references
References 40 publications
9
75
0
Order By: Relevance
“…[8,14] The similar bands can also be observed in 2 3+ (17 168 cm À1 , 14 427 cm À1 )b ut are blue-shifted, which results from the oxidation of the central Ru II into Ru III .The IVCT band of 1 3+ appears around l max = 5045 cm À1 (Table S7) and is narrow and asymmetrical. This is also the expected behavior for ac lass III MV compound, [8,15] suggesting the IVCT band arises from the electron resonance in the system rather than IVCT.The IVCT band of 2 3+ appears around l max = 8870 cm À1 (Table S7), and represents the ET processes between the terminal Ru II and the central Ru III .T his band is also cutoff and solvent independent ( Figure S10), indicating that 2 3+ may be ac lass II-III or class III MV compound. [2d,i, 8] These results indicate that the odd electron of 1 3+ may be delocalized and the central ruthenium shows some Ru III character.M oreover,t he IVCT energy is solvent independent ( Figure S9).…”
Section: Electrontransfer(et)isafundamentalprocessinchemistrysupporting
confidence: 79%
See 1 more Smart Citation
“…[8,14] The similar bands can also be observed in 2 3+ (17 168 cm À1 , 14 427 cm À1 )b ut are blue-shifted, which results from the oxidation of the central Ru II into Ru III .The IVCT band of 1 3+ appears around l max = 5045 cm À1 (Table S7) and is narrow and asymmetrical. This is also the expected behavior for ac lass III MV compound, [8,15] suggesting the IVCT band arises from the electron resonance in the system rather than IVCT.The IVCT band of 2 3+ appears around l max = 8870 cm À1 (Table S7), and represents the ET processes between the terminal Ru II and the central Ru III .T his band is also cutoff and solvent independent ( Figure S10), indicating that 2 3+ may be ac lass II-III or class III MV compound. [2d,i, 8] These results indicate that the odd electron of 1 3+ may be delocalized and the central ruthenium shows some Ru III character.M oreover,t he IVCT energy is solvent independent ( Figure S9).…”
Section: Electrontransfer(et)isafundamentalprocessinchemistrysupporting
confidence: 79%
“…In addition to the Robin and Day classification, Meyer et al proposed an ew category of the borderline class II-III systems that exhibit an intermediate behavior between class II and class III. [8] Recently,w eh ave reported an example of ad elocalized cyanide-bridged MV compound induced by thermal ET. [2i] To date,alarge number of MV compounds have been reported-most of which belong to class II systems.F or cyanido-bridged MV compounds, [2h,7] there are few well-characterized examples of fully delocalized (class III) MV systems.I n2 014, Baraldo and coworkers reported the first example of class III cyanidobridged species,which was confirmed by in situ near-infrared (NIR) and IR spectroscopy and supported by DFT calculations.…”
Section: Electrontransfer(et)isafundamentalprocessinchemistrymentioning
confidence: 99%
“…[6] Meantime, some important theory models have also been built. [5j,l, 8] As is well known, most of mixed valence compounds belong to Class II systems.Until most recently,Baraldo et al reported the first example of Class III cyanido-bridged species, [9] which was confirmed by NIR and IR spectroscopy and DFT calculations.Herein, we report anew cyanidometal bridged compound, trans-[Cp(dppe)Fe III NCRu II (obpy)CNFe III (dppe)Cp][PF 6 ] 4 (1[PF 6 ] 4 ). [5j,l, 8] As is well known, most of mixed valence compounds belong to Class II systems.Until most recently,Baraldo et al reported the first example of Class III cyanido-bridged species, [9] which was confirmed by NIR and IR spectroscopy and DFT calculations.Herein, we report anew cyanidometal bridged compound, trans-[Cp(dppe)Fe III NCRu II (obpy)CNFe III (dppe)Cp][PF 6 ] 4 (1[PF 6 ] 4 ).…”
mentioning
confidence: 87%
“…[7] Therein, polynuclear cyanido-bridged mixed valence complexes occupy an important position for the studied purpose. [5j,l, 8] As is well known, most of mixed valence compounds belong to Class II systems.Until most recently,Baraldo et al reported the first example of Class III cyanido-bridged species, [9] which was confirmed by NIR and IR spectroscopy and DFT calculations.Herein, we report anew cyanidometal bridged compound, trans-[Cp(dppe)Fe III NCRu II (obpy)CNFe III (dppe)Cp][PF 6 ] 4 (1[PF 6 ] 4 ). Its novel strong magnetic behavior and Mçssbauer spectra measurements confirm its Class III or delocalized mixed-valence species induced by intramolecular electron transfer from the central Ru II to the terminal Fe III in 1[PF 6 ] 4 .…”
mentioning
confidence: 87%
“…Cyanide salts such as KCN and NaCN are well known as po tential bridging material [6][7][8]. However, they are very poisonous.…”
Section: Introductionmentioning
confidence: 99%